Impact of Perceived Risks on Investors’ Usage Behaviour towards Online Trading Systems in Nepal - Magar, Pramesh Thapa; Tamang, Puja (Journal of Business and Social Sciences Research, 2025)
This study examines the impact of perceived risks on investors’ usage behaviour towards Nepal’s Trading Management System (TMS). It further analyses the extent to which this behaviour affects investors’ satisfaction. Using a quantitative approach, data were collected from 387 TMS users through structured questionnaires, and results were analysed using Partial Least Square Structural Equation Modelling (PLS-SEM). The findings show that financial and privacy risks do not significantly affect TMS usage, Time risk has an insignificant but positive impact. However, psychological risk negatively impacts usage. Interestingly, performance risk significantly and positively affects usage behaviour, indicating that investors may perceive system-related challenges as opportunities to learn or engage more actively in trading. The study also confirms a strong positive impact of TMS usage on investor satisfaction towards TMS. This study further highlights the need for reduced system errors as it provides better user experience. Regulatory bodies could enhance cybersecurity and investor protection, while educational programs can help investors to manage psychological risks and build confidence in digital trading.